The Relation between Self-efficacy and Quarter-Life Crisis in Final Year Students - Irwanti, Margareth Nafthalia; Siswanti, Dian Novita; Jafar, Eka Sufartianinsih (Polteknik Ilmu Pemasyarakatan, 2023)
Final-year students will enter a new phase, that is looking for work, getting married, and building a household. This mak es the students experience emotional tension such as stress, fear, anxiety, feeling doubtful about their own abilities in facing the future related to career, finances, and interpersonal relationships. This is usually known as the quarter-life crisis phase. Feeling doubt about abilities is an indication of self-efficacy. Self-efficacy is an individual's assessment of one's ability to solve problems, deal with tasks, and achieve goals. This study aims to determine the relationship between self-efficacy and quarter-life crisis in final-year students. This research uses quantitative methods. The number of respondents in this study was 307 final-year students from public and private universities. This research uses nonparametric statistical analysis to test Spearman’s rho. The results of the study show that there is a negative relationship between self-efficacy and quarter-life crisis in final-year students (r = -0.728 and p = 0.000). The higher the self-efficacy of final-year students, the lower quarter-life crisis experienced by final-year students, and vice versa. This research is expected to be a source of information for final year students in knowing the importance of increasing self-efficacy in dealing quarter life crisis phase.